Characterization of an integrated wearable sensor for biomechanics study - Guo, Wenjiang. (2009)
Humans rely on the feedbacks they received from a teacher in learning a new motor skill. The most effective way would be the tactile feedback system as it is direct and real-time which does not involve subjective self evaluation. However, this feedback is not widely available. Therefore, this project proposes a motor learning platform that can capture human motion and generate tactile feedback to direct, guide, and render movements. This motor learning platform integrates a motion capture system with a motion indicator. The motion indicator is made up of three coin-sized vibrating motors, which are termed as tactors. By circling them around the forearm and assigning each tactor two vibration patterns corresponding to an axial movement in the positive direction and in the negative direction respectively, it is able to create meaningful tactile feedback which gives users easily interpreted instruction on how to adjust their forearm postures and informs users of the correct forearm motion. The layout and vibration pattern design is evaluated through the usability test. It is concluded that the motion indicator creates an intuitive tactile feedback as well as capable of directing motion effectively. When the motion indicator is integrated with a motion capture system, the device can track and correct body postures to form an integrated wearable motion tracking device. It has applications in diverse areas, such as rehabilitation, and assists learning many motor skills that have requirement for movements with high accuracy. The integrated wearable motion tracking device has a promising future because of its wearability, effectiveness, small size, and low cost.